Ideological perspective on guideline “merdeka belajar – kampus merdeka” through systemic functional linguistics - Prayudisti Shinta Pandanwangi; Pratomo Widodo (LITERA, 2022)
This research exists to ignite the awareness and critical thinking from stakeholders and parties related to MBKM policies that have a long ideological impact on the life of higher education in Indonesia so that the implementers do not necessarily carry out policies without conducting assessments in depth first. Therefore, this study aims to explore and find the ideological and socio-political aspects behind the use of the lexicon in the Merdeka Learning guidebook – Merdeka Campus (MBKM) using textual metafunction and interpersonal metafunction approach model within Halliday's SFL framework (2004 2013). These textual and interpersonal approaches were chosen due to the scarcity of studies that apply this approach to analyze the discourse of this independent curriculum compared to studies of other disciplines. The data used in this study are in the form of lexicons used in the MBKM manual book as words or clauses within the chosen chapters. The result obtained is that the MBKM practical guidebook has a strong capitalist economic perspective. This is evidenced using lexicons that indicate the direction of higher education to be achieved tends to follow the circulation of the free market and higher education and all stakeholders involved are regulated to follow this globalization trend. “Independent Campus – Merdeka Learning” requires students to be able to equip themselves to survive life's challenges. In contrast, the campus as an “intellectual factory” is always billed for the needs of the industrial sector, not a place for “true intellectuals”.Keywords: SFL, CDA, independent learning – independent campus, capitalization of higher education Perspektif ideologis tentang pedoman "merdeka belajar – kampus merdeka" melalui linguistik sistemik fungsionalAbstrakPenelitian ini hadir untuk memantik kesadaran dan nalar berpikir kritis dari para pemangku kepentingan serta pihak-pihak yang terkait dengan kebijakan MBKM yang dipandang memiliki dampak ideologis jangka Panjang terhadap hidup dari Pendidikan tinggi di Indonesia, dan agar para pelaksana tidak serta merta menjalankan kebijakan tanpa melakukan pengkajian secara mendalam terlebih dahulu. Maka dari itu kajian ini bertujuan untuk mengeksplorasi dan menemukan aspek ideologis dan sosio-politis di balik penggunaan leksikon dalam buku panduan Merdeka Belajar – Kampus Merdeka (MBKM) dengan menggunakan model pendekatan textual metafunction dan interpersonal metafunction dalam kerangka SFL milik Halliday (2004 2013). Pendekatan tekstual dan interpersonal ini dipilih dikarenakan masih langkanya kajian yang mengaplikasikan pendekatan ini untuk menganalisis diskursus kurikulum merdeka ini dibandingkan dengan kajian disiplin ilmu yang lain. Data yang digunakan dalam kajian ini berbentuk leksikon-leksikon yang digunakan dalam buku panduan MBKM baik berupa kata atau klausa pada bab yang dipilih. Hasil yang diperoleh adalah buku panduan praktis MBKM tersebut memiliki perspektif ekonomi kapitalis yang cukup kuat. Hal ini dibuktikan adanya penggunaan leksikon-leksikon yang menunjukkan arah pendidikan tinggi yang hendak diraih cenderung mengikuti sirkulasi pasar bebas dan pendidikan tinggi beserta seluruh stakeholder yang terlibat diregulasi agar mengikuti tren globalisasi ini. “Kampus Merdeka – Merdeka Belajar” menuntut mahasiswa untuk dapat membekali diri agar mampu bertahan menghadapi tantangan hidup, sedangkan kampus sebagai “pabrik intelektual” selalu ditagih untuk kebutuhan sektor industri bukan tempat untuk “ intelektual sejati".Kata kunci: SFL, CDA, merdeka belajar – kampus merdeka, kapitalisasi pendidikan tinggi